2019
DOI: 10.1371/journal.pone.0215765
|View full text |Cite
|
Sign up to set email alerts
|

Structural and diffusion weighted MRI demonstrates responses to ibrutinib in a mouse model of follicular helper (Tfh) T-cell lymphoma

Abstract: Recent analyses of the genetics of peripheral T-cell lymphoma (PTCL) have shown that a large proportion of cases are derived from normal follicular helper (Tfh) T-cells. The sanroque mouse strain bears a mutation that increases Tfh cell number and heterozygous animals (Roquin san/+ ) develop lymphomas similar to human Tfh lymphoma. Here we demonstrate the usefulness of Roquin san/+ animals as a pre-clinical model of Tfh lymphoma. Long latency of development and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The tyrosine kinase inhibitor dasatinib has been shown to block VAV1 phosphorylation and increased TCR signalling due to RHOA (p.Gly17Val) in a T‐cell line (Fujisawa et al , ). ITK is expressed in AITL and we have demonstrated in cell lines (Mamand et al , ) and also in a mouse model of Tfh lymphoma (Allchin et al , ) that ibrutinib, a dual ITK and Bruton's tyrosine kinase (BTK) inhibitor, can repress growth and reduce tumour size. A clinical trial that enrolled patients with a mixture of T‐cell lymphoma diagnoses did not support the use of ibrutinib (Kumar et al , ) but the effects of this drug on specific AITL populations is unknown.…”
Section: Routes To the Clinicmentioning
confidence: 97%
“…The tyrosine kinase inhibitor dasatinib has been shown to block VAV1 phosphorylation and increased TCR signalling due to RHOA (p.Gly17Val) in a T‐cell line (Fujisawa et al , ). ITK is expressed in AITL and we have demonstrated in cell lines (Mamand et al , ) and also in a mouse model of Tfh lymphoma (Allchin et al , ) that ibrutinib, a dual ITK and Bruton's tyrosine kinase (BTK) inhibitor, can repress growth and reduce tumour size. A clinical trial that enrolled patients with a mixture of T‐cell lymphoma diagnoses did not support the use of ibrutinib (Kumar et al , ) but the effects of this drug on specific AITL populations is unknown.…”
Section: Routes To the Clinicmentioning
confidence: 97%
“…A topical retinoid was shown to inhibit ITK and reduce tumor growth in a murine model of cutaneous T cell lymphoma (Li et al, 2020). Another study showed that ITK inhibition worked synergistically with chemotherapy in a T cell lymphoma xenograft model (Liu et al, 2019), and ibrutinib was shown to shrink tumor burden using a novel T cell lymphoma murine model (Allchin et al, 2019). However, despite these findings, a recent pilot study found that 14 patients with refractory T cell lymphoma failed to respond to ibrutinib (Kumar et al, 2018).…”
Section: T Cell Lymphoma and A Novel Immunotherapeutic Approach Peripheral T Cell Lymphomamentioning
confidence: 99%
“…A large proportion of PTCL cases are derived from follicular helper T cells (Tfh), which express high levels of ITK proteins (66). In a mouse model of Tfh-derived lymphoma, ibrutinib effectively induces lymphoma regression (67). However, the preliminary results of the Phase I trial NCT02309580 suggest that ibrutinib has limited clinical benefits in 13 patients with R/R TCL (49) (Table 2).…”
Section: Hematological Malignancies Of Myeloid Cells and T Cellsmentioning
confidence: 99%